High levels of heterogeneity in the HIV cascade of care across different population subgroups in British Columbia, Canada. - Lillian Lourenço; Guillaume Colley; Bohdan Nosyk; Dmitry Shopin; Julio S G Montaner; Viviane D Lima; STOP HIV/AIDS Study Group (PLoS ONE)
Background The HIV cascade of care (cascade) is a comprehensive tool which identifies attrition along the HIV care continuum. We executed analyses to explicate heterogeneity in the cascade across key strata, as well as identify predictors of attrition across stages of the cascade. Methods Using linked individual-level data for the population of HIV-positive individuals in BC, we considered the 2011 calendar year, including individuals diagnosed at least 6 months prior, and excluding individuals that died or were lost to follow-up before January 1st, 2011. We defined five stages in the cascade framework: HIV 'diagnosed', 'linked' to care, 'retained' in care, 'on HAART' and virologically 'suppressed'. We stratified the cascade by sex, age, risk category, and regional health authority. Finally, multiple logistic regression models were built to predict attrition across each stage of the cascade, adjusting for stratification variables. Results We identified 7621 HIV diagnosed individuals during the study period; 80% were male and 5% were <30, 17% 30-39, 37% 40-49 and 40% were ≥ 50 years. Of these, 32% were MSM, 28% IDU, 8% MSM/IDU, 12% heterosexual, and 20% other. Overall, 85% of individuals 'on HAART' were 'suppressed'; however, this proportion ranged from 60%-93% in our various stratifications. Most individuals, in all subgroups, were lost between the stages: 'linked' to 'retained' and 'on HAART' to 'suppressed'. Subgroups with the highest attrition between these stages included females and individuals <30 years (regardless of transmission risk group). IDUs experienced the greatest attrition of all subgroups. Logistic regression results found extensive statistically significant heterogeneity in attrition across the cascade between subgroups and regional health authorities. Conclusions We found that extensive heterogeneity in attrition existed across subgroups and regional health authorities along the HIV cascade of care in B.C., Canada. Our results provide critical information to optimize engagement in care and health service delivery.